The Effects of Microplastic Chemical Waste on the Environment : Literature Review - Indah, Dahlia Rosma; Rayani, Dewi; Nurwahidah, Nurwahidah (Universitas Pendidikan Mandalika, 2025)
Microplastics are plastic flakes or crumbs with a size smaller than 5 millimeters that come from large plastic fragments such as crackle bags, clear plastic, clothing waste, plastic bottles, styrofoam and sachets that are fragmented due to water currents and sun exposure. The danger of microplastics when they enter water, can absorb heavy metals and pollutants in the water, such as Chlorine, Phosphate, Manganese, and Chromium. As a result, the water ecosystem will be disrupted. If microplastics are ingested by fish, the fish's reproductive and growth systems are damaged. Moreover, it can interfere with human hormones if you consume the fish. The test was carried out using the Microplastic Rapid Test method using a stereo microscope connected to a monitor, so that with a magnification of 100 to 400 times, it can physically detect microplastics in the water. This researcher is a literature review. The database used in the search for this article uses Google Scholar and ScienceDirect with the keywords